Growth of long-length sapphire rods of optical quality - Andreev, Yu.P.; Kryvonosov, Yu.V.; Lytvynov, L.A.; Vyshnevskiy, S.D. (Functional Materials, 2005)
The technological possibilities of the growth of optical-quality sapphire rods with a diameter of 12...20 mm and a length of 500...1000 mm by the Stepanov method. The influence of crystallization rate and crystallographic growth direction on the optical quality of the crystals was investigated. The technological procedure of "cold" narrowing of the growing crystal at the beginning stage of seeding was proposed to improve crystals structure. It was shown that heat treatment of the grown crystal in a gas environment with neutral chemical potential leads to destruction of optical color centers and scattering foreign-phase inclusions in its volume. It was shown that the main reason of color and scattering centers foundation in sapphire is anionic stoichiometry violation and the presence of uncontrollable impurities in the melt._To obtain long sapphire rods of optical quality the crystallographic oriented growth [1120] is preferred. In the process of growing a rod with a diameter of 14 mm, the depth of the surface-adjacent defective layer does not exceed 0.4 mm and the small-angle optical scattering doesn’t have to be greater than 0.01 cm⁻¹. Рассмотрены технологические возможности выращивания стержней сапфира оптического качества диаметром 12...20 мм и длиной 500...1000 мм методом Степанова. Исследовано влияние кристаллографического направления роста и скорости кристаллизации на оптическое качество кристаллов. Предложен технологический метод "холодной перетяжки" растущего кристалла на этапе затравления для улучшения его структурного совершенства. Показано, что термообработка выращенного кристалла при нейтральном химическом потенциале среды отжига позволяет разрушить оптические центры окраски и рассеивающие инофазные включения в его объёме. Установлено, что основной причиной образования центров окраски и рассеивающих центров в сапфире является анионная расстехиометрия расплава и наличие в нём сопутствующих неконтролируемых примесей. Для получения длинномерных сапфировых стержней оптического качества предпочтительным кристаллографическим направлением роста является [1120]. При выращивании стержня диаметром 14 мм толщина приповерхностного дефектного слоя не превышает 0,4 мм, а малоугловое оптическое рассеяние не более 0,01 см⁻¹. Розглянуто технологічні можливості вирощування стержнів сапфіру оптичної якості діаметром 12...20 мм і довжиною 500...1000 мм методом Степанова. Досліджено вплив кристалографічного напрямку росту і швидкості кристалізації на оптичну якість кристалів. Запропоновано технологічний метод "холодного перетягнення" кристала, що росте, на етапі затравлення для поліпшення його структурної довершеності. Показано, що термообробка кристала при нейтральному хімічному потенціалі середовища відпалу дозволяє зруйнувати оптичні центри забарвлення і розсіюючі інофазні включення в його об’ємі. Встановлено, що основною причиною утворення центрів забарвлення і розсіюваю-чих центрів у сапфірі є аніонна розстехіометрія розсплаву та присутність в ньому некон-трольованих домішок. Для отримання довгомірних сапфірових стержнів оптичної якості необхідно віддавати перевагу кристалографічному напрямку росту [1120]. При вирощуванні стержня діаметром 14 мм товщина приповерхневого шару не перебільшує 0,4 малокутове оптичне розсіювання не більш ніж 0,01 см⁻¹.